1995
DOI: 10.1177/106002809502900407
|View full text |Cite
|
Sign up to set email alerts
|

Clinafloxacin-Theophylline Drug Interaction

Abstract: The observation of this drug interaction between clinafloxacin and theophylline suggests a need for prudent monitoring of theophylline concentrations. Dosage adjustments may be warranted when this combination of medications is used. Such action may prevent significant toxicities and prolonged hospitalization. Further controlled clinical trials in healthy volunteers are needed to substantiate the interaction between clinafloxacin and theophylline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Comparison of the structure of clinafloxacin with those of several marketed and experimental quinolone antibiotics suggests a "very high" relative potential for a theophylline interaction. Inhibition of theophylline metabolism was reported in a clinafloxacin clinical study (25). Theophylline concentrations in plasma increased nearly twofold during clinafloxacin therapy compared to those observed prior to clinafloxacin therapy.…”
mentioning
confidence: 83%
“…Comparison of the structure of clinafloxacin with those of several marketed and experimental quinolone antibiotics suggests a "very high" relative potential for a theophylline interaction. Inhibition of theophylline metabolism was reported in a clinafloxacin clinical study (25). Theophylline concentrations in plasma increased nearly twofold during clinafloxacin therapy compared to those observed prior to clinafloxacin therapy.…”
mentioning
confidence: 83%
“…A 600 mg daily dose of ciprofloxacin has been observed to cause an increase in the C max and AUC of theophylline of 17% and 22%, respectively (242). Clinafloxacin (200 mg every 12 h) was reported to produce a more than doubling of serum theophylline concentration in one case report (241). Finally, grepafloxacin (600 mg every day) has been reported to increase the C max of theophylline by 82% and to decrease the total theophylline clearance by about 50% (243).…”
Section: Metal Ion-containing Drugsmentioning
confidence: 98%
“…If this is not feasible, the fluoroquinolone should be administered at least 2 h before or 6 h after the ingestion of the metal ion-containing drug (6,236,240). Theophylline: The metabolic enzyme cytochrome P450 1A2 can be inhibited by several of the fluoroquinolones (ciprofloxacin, clinafloxacin, grepafloxacin), resulting in reduced clearance of theophylline (241,242). This can lead to increased serum theophylline levels and potential toxicity (6,241).…”
Section: Metal Ion-containing Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1984, Wijnands et al first reported severe clinical adverse effects with the concomitant use of TP and enoxacin, and they found that co-administration of enoxacin markedly increased plasma TP concentrations [11] . Consequently, a series of fluoroquinolones, including ciprofloxacin, tosufloxacin, clinafloxacin, grepafloxacin, and pefloxacin, have been reported to interfere with TP metabolism by inhibiting CYP1A2 activity [12][13][14][15] . Therefore, it is important to evaluate the interaction between ATFX and TP to understand the pharmacokinetics and safety of these drugs.…”
Section: Modulation Of Pharmacokinetics Of Theophylline By Antofloxacmentioning
confidence: 99%